W. Morgan Shuster papers - Shuster, W. Morgan (William Morgan), 1877-1960.; Douglass, Elisha P.
Correspondence (1911-1964), diary (1911-1912), scrapbooks (1900-1923, 10 volumes), certificates (1901-1951), and other papers documenting Shuster's diplomatic career as treasurer-general and financial advisor for Persia (1911-1912) and his earlier posts in the customs service in Cuba (1899-1901) and as insular collector of customs in Manila and member of the Philippine Commission (1901-1909). Includes letters from William H. Taft and Woodrow Wilson and from family members. Also includes an unpublished thesis by Elisha P. Douglass entitled, "Anglo-Russian Friction, 1907-1911, and the Morgan Shuster Affair."
Scrapbooks available only on microfilm
Microfilm produced from scrapbooks in the Manuscript Division.
Diplomat, financier, lawyer, and publisher.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Taft, William H. -- 1857-1930 -- Correspondence; Wilson, Woodrow, -- 1856-1924 -- Correspondence; United States. -- Philippine Commission (1900-1916); Customs administration -- Cuba; Customs administration -- Philippines -- Manila; Diplomatic and consular service, American -- Iran; Finance -- Iran; Great Britain -- Foreign relations -- Russia; Iran -- Economic conditions; Iran -- History -- 1905-1911.; Russia -- Foreign relations -- Great Britain; Diplomats; Financiers; Lawyers; Publishers